(untitled) (Comparatismi, 2025)
This study aims to analyse the various functions that heterolingualism – that is the incursion of one or more foreign languages into a text – can assume in the works of three Franco-Italian plurilingual authors from the first half of the XXth century. The comparative approach adopted allows for the juxtaposition of different generic types under this device: Filippo Tommaso Marinetti’s mature memoir Una sensibilità italiana nata in Egitto, Alberto Savinio’s bilingual prosimetrum Hermaphrodito, and Curzio Malaparte’s novel La pelle. The text further explores the connections between heterolingualism and genre in Franco-Italian literature, situating them within contemporary theories of translingual genres.